PERTUMBUHAN DAN PRODUKSI CABAI (Capsicum annuum L.) DENGAN PEMBERIAN LIMBAH CAIR BIOGAS DAN PUPUK NPK DI TANAH GAMBUT - Ikhsan Dwi Andianto; Armaini '; Fifi Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to know the effect of  bioslurry interaction and the NPK fertilizer and get the best combination on the growth and production of chili (Capsicum annuum L.) in peat soil.  This research was experimentaly using a Completely Randomized Design (CRD), which consists of two factors. The first factor is giving of bioslurry consisting  of  three  levels: L0 = (0 tons/ha)  bioslurry,  L1= 200  g/polybag (10 tons/ha)  bioslurry,  L2 = 400 g/polybag (20 tons/ha)  bioslurry. The second factor is the NPK fertilizer which consists of three levels  N1 = 3 g/polybag (150 kg/ha) NPK, N2 = 4 g/polybag (200 kg/ha) NPK, N3 = 5 g/polybag (250 kg/ha) NPK. There were 9 combination treatments with three  replications then obtained 27 experimental units, the experimental units consisted of two plants, so that the total population were 54 plants. Parameters measured were stem diameter, height dichotomous, plant height, days to flowering, harvesting, fruit diameter, fruit length, number of fruits per plant, total fruit weight per plant and fruit weight per plant worthy consumption.  Interaction of  treatment bioslurry and fertilizer NPK does not give effect to all parameters. Based on the research in order to get the growth and production of chili plants can be use a combination of bioslurry 20 tons/ha and 250 kg/ha NPK Keywords: Bioslurry, NPK fertilizer, chili and peat soil